(untitled) (Third Sector Social Economic Review, 2026)
Museum experience has become an important recreational activity in today’s society. This study aims to identify the factors influencing service quality and visitor experience at the Great Palace Mosaic Museum. To achieve this objective, the netnographic method was employed. A total of 379 English-language reviews posted on the TripAdvisor website by visitors to the Great Palace Mosaic Museum were examined with content analysis. First, line-by-line coding was performed, and then themes were identified using the resulting codes. The results of the study revealed that visitors’ perceptions of service quality were categorized under tangibles, communication, responsiveness, consumables, and empathy, while the factors influencing the visitors experience were grouped under post-experience evaluations, emotions, cognitive, flow, and memorability. Among the service quality components, tangibles was found to be the most prominent, whereas empathy was the least frequently mentioned dimension. In the findings regarding visitor experiences, post-experience evaluations and cognitive dimensions emerged as the most prominent dimensions. Flow and memorability were identified as factors arising within the museum experience. Present study is one of the first studies to examine visitors’ perceptions of service quality and their overall experience at a museum that focuses exclusively on mosaics. This study contributes to the understanding of visitor experience and their service quality perception in museums.